1979
DOI: 10.1128/jb.137.1.285-294.1979
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Glycolytic Intermediates, Glycolytic Enzymes, and Ammonia to Glycogen Metabolism During Sporulation in the Yeast Saccharomyces cerevisiae

Abstract: To identify the factors which control glycogen synthesis in Saccharomyces cerevisiae, we have studied the regulation of glycogen metabolism during sporulation, since in vivo glycogen has been reported to undergo significant changes in concentration during this process. We examined the concentration of a number of key glycolytic intermediates and enzymes in strains that sporulate at different rates and those that are deficient in sporulation. There were no significant changes found in the adenylate energy charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Ammonium ion plays a primary role in nitrogen metabolism in general by controlling the amino acid pool (13) but also appears to affect sporulation (secondary metabolism) specifically (19) by blocking the normal increases in proteases that occur in yeast cells after transfer to sporulation medium (15). Ammonium ion also inhibits RNA and protein synthesis during sporulation (9) as well as sporulation-specific glycogen degradation (11) and induction of glyoxylate enzymes during adaptation to acetate in Saccharomyces (12).…”
Section: Vol 142 1980mentioning
confidence: 99%
“…Ammonium ion plays a primary role in nitrogen metabolism in general by controlling the amino acid pool (13) but also appears to affect sporulation (secondary metabolism) specifically (19) by blocking the normal increases in proteases that occur in yeast cells after transfer to sporulation medium (15). Ammonium ion also inhibits RNA and protein synthesis during sporulation (9) as well as sporulation-specific glycogen degradation (11) and induction of glyoxylate enzymes during adaptation to acetate in Saccharomyces (12).…”
Section: Vol 142 1980mentioning
confidence: 99%
“…
The addition of 10 mM ammonium sulfate to sporulation medium noncoordinately blocked the increases in protease C, protease B, ai-mannosidase, and 1,4amyloglucosidase activities which occur during normal sporulation of Saccharomyces cerevisiae, but had only a minor effect on the 10-fold increase in alkaline phosphatase activity.Sporulation of Saccharomyces cerevisiae has long been known to be inhibited by the addition of a nitrogen source to sporulation medium (13). NH4' blocks DNA, RNA, and protein syntheses (3,4,15), as well as the increase in protein (3) and glycogen degradation (5, 9) which occurs during normal sporulation. We have previously shown that NH4' has only a minimal effect on energy and glycolytic pathway metabolites in cells incubated in sporulation medium supplemented with NH4' (5).
…”
mentioning
confidence: 99%
“…Sporulation of Saccharomyces cerevisiae has long been known to be inhibited by the addition of a nitrogen source to sporulation medium (13). NH4' blocks DNA, RNA, and protein syntheses (3,4,15), as well as the increase in protein (3) and glycogen degradation (5,9) which occurs during normal sporulation. We have previously shown that NH4' has only a minimal effect on energy and glycolytic pathway metabolites in cells incubated in sporulation medium supplemented with NH4' (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations